STRUKTUR KECEPATAN GELOMBANG S DI DAERAH DEPAN BIDANG SUBDUKSI ALASKA DENGAN MENGANALISA SEISMOGRAM GEMPA C022801L DI STASIUN WHY - Santosa, Bagus Jaya (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
In this research the measured seismogram of C022801L, Washington U.S.A. is compared to the synthetic seismogram, which is recorded at WHY observation station in three dimensions, where the wave path resides in front area of Alaska subduction zone. The synthetic seismogram is calculated with the GEMINI Program, whose input is in the form of an earth model, which is radial symmetry and transversal isotropic, and the CMT solution of the quake.Simulation and seismogram comparison can only be conducted till a frequency to 15 mHz, because big discrepancies are found at surface wave and the depth wave phase ScS. The surface wave propagates along earth surface till a depth which is equivalent to depth of upper mantle; so that the fitting can be obtained by altering speed structure till base of upper mantle, where the corrections are conducted at bh speed gradient. Correction at upper mantle structure does not bring repair at wave phase ScS. Corrective is further executed at speed structure of shear wave S till CMB, until the good fitting at ScS wave is obtained. S velocity structure in front area of Alaska subduction zone has in reality a strong positive anomaly, and to get fitting at ScS wave, the positive anomaly continues at earth layers below upper mantle till CMB